2019
DOI: 10.1002/bies.201900088
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Inhibitory Projections Guide Sensorimotor Computation: An Invertebrate Perspective

Abstract: From single-cell organisms to complex neural networks, all evolved to provide control solutions to generate context-and goal-specific actions. Neural circuits performing sensorimotor computation to drive navigation employ inhibitory control as a gating mechanism as they hierarchically transform (multi)sensory information into motor actions. Here, the focus is on this literature to critically discuss the proposition that prominent inhibitory projections form sensorimotor circuits. After reviewing the neural cir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 135 publications
(259 reference statements)
1
7
0
Order By: Relevance
“…Similar to other studies, we found that isolation increased ambulation in an open field as well as the number of arm entries in an EPM (Ieraci et al., 2016; Shao et al., 2009). Ambulation and navigation are complex behaviors that involve whole brain computation (Hughes & Celikel, 2019) and are dependent on the activation of sensorimotor circuits (Hughes & Celikel, 2019). Pre‐pulse inhibition (PPI) is used as an operational measure of sensorimotor gating (Fitzgerald & Pickel, 2018; Kohl et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies, we found that isolation increased ambulation in an open field as well as the number of arm entries in an EPM (Ieraci et al., 2016; Shao et al., 2009). Ambulation and navigation are complex behaviors that involve whole brain computation (Hughes & Celikel, 2019) and are dependent on the activation of sensorimotor circuits (Hughes & Celikel, 2019). Pre‐pulse inhibition (PPI) is used as an operational measure of sensorimotor gating (Fitzgerald & Pickel, 2018; Kohl et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the sensorimotor deficits might be a consequence of an altered balance between excitation and inhibition (E/I) as elevated serotonin levels during development impairs feedforward inhibition and facilitate excitatory drive in the somatosensory system (Miceli et al, 2017). Considering that altered E/I balance is critical for preventing runaway excitation, sharpening stimulus selectivity, and increasing the overall sparseness of stimulus representations, a local change in E/I balance in sensory systems might have global consequences on the perceptual, cognitive and motor deficits Murray et al, 2014;Juczewski et al, 2016;Lainscsek et al, 2019), even in invertebrates (Hughes and Celikel, 2019). Given the regulatory close-loop between serotonergic drive and sensory experience (Yan et al, submitted) the impact of the transient alterations in E/I balance could be sustained in longer time scales.…”
Section: Altered Excitation/inhibition Balance Might Explain Serotonementioning
confidence: 99%
“…Dopamine is a monoaminergic neurotransmitter that regulates a wide range of neurophysiological functions such as behaviour, attention, cognition (1)(2)(3)(4). Low levels of dopamine in the brain are known to cause neurological and psychological disorders like Parkinson's, Alzheimer's diseases and schizophrenia (5).…”
Section: Introductionmentioning
confidence: 99%